THE IMPLEMENTATION OF BLOWFISH ALGORITHM IN CLIENT SERVER NETWORK-BASED FILE SECURITY - Novrizam Hari; Khairil Khairil; Arius Satoni Kurniawansyah (GATOTKACA Journal (Teknik Sipil, Informatika, Mesin dan Arsitektur), 2021)
SMAN 1 of Central Bengkulu, is already connected via LAN network, an academic assessment system that deals with student scores on monthly test results, midterm tests (UTS), final semester tests (UAS), at this time it is considered inefficient and does not have security data. where each staff / teacher will exchange information via computers such as sharing / exchanging document files such as student grade data. The document file is not given a password so that anyone can open that file. Therefore we need a security system for sharing document files, because the files sent can be opened by anyone. In responding to the problems, a system security will be designed by applying the Blowfish Cryptography (modern cryptography) algorithm which is expected to be a solution to the problems being faced. By using the Blowfish Cryptography algorithm, it is hoped that it can help to protect the original file so that it is not easily read by unauthorized people.